COPAYMENTS OF THE CITIZENS IN HEALTHCARE SYSTEM: INTERNATIONAL PRACTICE - A. P. Tatarinov; D. V. Lukyantseva; L. S. Melnikova; V. V. Omelyanovskii (Фармакоэкономика, 2016)
The growth of cost of healthcare services becomes more and more serious problem throughout the world. In the context of no limitations with respect to both scope of consumption and cost of the services, due to application of innovational treatment methods, the cost of medical aid, rendered to the citizens free of charge, has almost no upper limit. In light of this, the alternative strategies of more efficient and fair funding of healthcare, being the subject of this article, are searched throughout the world.